ChemInform Abstract: New Quaternary Alkali‐Metal Hypodiphosphate Hydrates: Preparation, Crystal Structure, Vibrational Spectrum, and Thermal Behavior of K4P2O6·8H2O and Na2K2P2O6·8H2O in Comparison to Na4P2O6·10H2O. Issue 3 (22nd January 2013) - Gjikaj, Mimoza; Wu, Peng; Brockner, Wolfgang
Abstract Single crystals of K4P2O6·8H2O and Na2K2P2O6·8H2O are prepared by addition of KOH to an aqueous solution of hypodiphosphoric acid (20 °C) resp.